2019
DOI: 10.1007/s42452-019-0514-4
|View full text |Cite
|
Sign up to set email alerts
|

Fast start-up of anammox process with hydrazine addition

Abstract: The anammox process is an economically favourable nitrogen removal process; however, low growth rates of anammox biomass block its more widespread application. As different approaches on techniques for anammox bacteria growth acceleration were tested, this study focused on long-term evaluation of hydrazine addition in the start-up phase. Effect of hydrazine addition (dose 3.7 mgN 2 H 4 dm −3 ) was investigated in a pilot-scale SBR treating ammonia-rich reject water from sludge dewatering after partial nitritat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…N 2 H 4 can also be used to recover and enhance the autotrophic N‐removal capacity by promoting anammox enzyme activity after exposure and inhibition by high NO 2 − concentrations. Miodoński et al (2019) demonstrated that the addition of 3.7 mg N 2 H 4 L −1 in an anammox reactor promoted an increase in the specific activity of anammox (22.6%) compared with a system without the addition of N 2 H 4 ; Yao et al (2013) also verified the positive effects of the addition of N 2 H 4 in the anammox process, with an increase of approximately 12% in the efficiency of N‐removal with the addition of 3.99 mg N 2 H 4 L −1 . According to Ma et al (2018), the addition of N 2 H 4 promoted the generation of azide in the presence of NO 2 − , accelerating the activity of AnAOB in the degradation of NO 2 − , mainly inhibiting the activity of NXR, thus reducing the formation of NO 3 − .…”
Section: Anammox Processmentioning
confidence: 99%
“…N 2 H 4 can also be used to recover and enhance the autotrophic N‐removal capacity by promoting anammox enzyme activity after exposure and inhibition by high NO 2 − concentrations. Miodoński et al (2019) demonstrated that the addition of 3.7 mg N 2 H 4 L −1 in an anammox reactor promoted an increase in the specific activity of anammox (22.6%) compared with a system without the addition of N 2 H 4 ; Yao et al (2013) also verified the positive effects of the addition of N 2 H 4 in the anammox process, with an increase of approximately 12% in the efficiency of N‐removal with the addition of 3.99 mg N 2 H 4 L −1 . According to Ma et al (2018), the addition of N 2 H 4 promoted the generation of azide in the presence of NO 2 − , accelerating the activity of AnAOB in the degradation of NO 2 − , mainly inhibiting the activity of NXR, thus reducing the formation of NO 3 − .…”
Section: Anammox Processmentioning
confidence: 99%
“…However, most of the above-mentioned studies were based on the results of small-scale tests obtained from sequential batch experiments, and pilot tests or engineering application data for continuous water inflow have rarely been reported. Anammox bacteria are extremely sensitive to their living environment (Khramenkov et al, 2013;Miodoński et al, 2019;Strous et al, 1998). In pilot-scale and engineering applications, due to changes in the reactor and its operating conditions, relevant research results would likely differ somewhat, or even significantly, from those of small-scale tests.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to shorten the start-up time of the Anammox process, many researchers have focused on optimizing key parameters such as seeding sludge, operational strategy, biomass immobilization, etc. (Verma et al 2021), and the addition of chemical reagents into the system for stimulating the bacteria (Ganesan & Vadivelu 2019;Miodonśki et al 2019). Therefore, in full-scale applications of Anammox process, in case of a sudden toxicity, recovery would be a better way than restarting it.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%